THE EFFECT OF THE APPLICATION OF PUBLIC SECTOR ACCOUNTING, ACCOUNTABILITY, AND PERFORMANCE TRANSPARENCY ON THE QUALITY OF FINANCIAL STATEMENTS IN COLOMADU SUB-DISTRICT - Desnardo Ivan Prabowo; Suprihati Suprihati; Darmanto Darmanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to analyze the effect of the application of public sector accounting, accountability, and performance transparency on the quality of financial reports. The population in this study were village officials and staff at the village office in Colomadu District. Determination of the sample in this study using the simple random sampling method is a sampling technique used by researchers to provide equal opportunity to all member of the population to be selected as member of the sample. The sample coscisted of Lurah/Village Head, Hamled Head, Head of Planning Affairs, and staff. The analysis uses multiple linear regression with a significant level (α) of 0,05. The result of this study indicate that : (1) the application of public sector accounting affect the quality of financial report, this is because the application of public sector accounting can explain the quality of financial reports in government agencies, and also to improve government accounting in the future, (2) accountability affects the quality of financial reports as a form of accountability , (3) performance transparency does not affect the quality of financial reports. Keywords: Public sector accounting, accountability, transparency, report quality finance